Energy, Exergy and Exergo-Economic Characteristics of Hydrogen Enriched Hydrocarbon-Based Fuels in a Premixed Burner - YILMAZ, İLKER TURGUT; ÖZDEMİR, MEHMED RAFET; YANGAZ, MURAT UMUT (TAYLOR & FRANCIS INC, 2021)
The enrichment of conventional fuels by hydrogen is quite popular owing to positive environmental aspects compared to the main fuel. In most of the studies, the entropy analysis was not examined in detail. In this research, exergy (second law) analysis of hydrogen-enriched methane, natural gas, propane, LPG, and biogas were analyzed using the numerical model in a premixed burner due to their wide usage in the industry as well as in the household appliances. In the numerical model, the discrete ordinates radiation and Realizable k- epsilon turbulence models were coupled with the premixed combustion model. The rate of increase for hydrogen of each fuel is considered as 10%. The premixed burner exhibited better performance in terms of energy and exergy with the rise of hydrogen enrichment. The most improvement was observed at biogas tests. The results showed that the chemical composition of the base fuel is a significant parameter that affects the exergy and energy capability of the burner due to chain reactions of radicals in the base fuel with hydrogen. It can be concluded that the hydrogen enrichment of biogas in premixed burners is promising in comparison with other tested fuels from both energy and exergy perspective.
Keywords: Hydrogen enrichment; energy analysis; exergy analysis; exergo-economic analysis; premixed burner; combustion